1996
DOI: 10.1139/z96-197
|View full text |Cite
|
Sign up to set email alerts
|

Use of woody plants in construction of beaver dams in northern Ontario

Abstract: Newly formed beaver dams were studied in the Chapleau Crown Game Preserve of northern Ontario to determine if beavers (Castor canadensis Kuhl) showed any preference in their choice of woody plants in building the dams. Application of Neu's utilization–availability technique showed that beavers exhibited a high preference for alder (Alnus spp., plant species not commonly used as food) stems with diameters of 1.5–3.5 cm and a lesser preference for food-tree stems with diameters of >4.5 cm. We maintain that be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…As suggested by reports in the literature [12,13,15,21] and our hypotheses, the effects of geomorphological and hydrological parameters were the most significant in predicting the presence of beaver dams near culverts. In addition, we observed that coarse variables from the DEM (HYDRO1) were not sufficient to make valid predictions.…”
Section: Variables Predictive Power and Support Of Submitted Hypothesessupporting
confidence: 78%
“…As suggested by reports in the literature [12,13,15,21] and our hypotheses, the effects of geomorphological and hydrological parameters were the most significant in predicting the presence of beaver dams near culverts. In addition, we observed that coarse variables from the DEM (HYDRO1) were not sufficient to make valid predictions.…”
Section: Variables Predictive Power and Support Of Submitted Hypothesessupporting
confidence: 78%
“…These results for trembling aspens in our study is more readily explained by the observations that for large trees, beavers often only took back canopy branches and leaves as well as secondary branches back to the pond and that bark on the main trunk appears to be ingested on site (D. Gallant, personal observation). It is common to observe large trunks lying where beavers felled them, whereas research shows that smaller trees are more readily found at the pond in dams and huts (Barnes and Mallik 1996). In addition, large trees can serve for more than one visit to the foraging area without additional search effort.…”
Section: Discussionmentioning
confidence: 99%
“…Speckled alder was also excluded because this species is not primarily selected for nutritional purposes, as shown by the majority of alder stems found with intact bark on lodges and dams in our study (D. Gallant, personal observation). Beavers select it mainly as structural material for dams and lodges (Doucet et al 1994b; Barnes and Mallik 1996) or for structural support in food caches (Slaugh 1978) rather than for immediate consumption. Availability of accessible building material for initial construction of dams and lodges affects the beavers' choice of habitat in terms of establishment location, as shown by Barnes and Mallik's (1997) study where beavers relied on shoreline concentrations of woody plants 1.5-4.4 cm in diameter.…”
Section: Discussionmentioning
confidence: 99%
“…Smaller woody stems (54 cm diameter) are preferred (Basey and Jenkins, 1995;Barnes and Mallik, 1996), and the size of pieces cut decreases with increasing distance from water (Jenkins, 1980). Similarly, vegetation as a food source for C. fiber is suggested by Stocker (1983) to be a crucial issue in attempts at reintroduction.…”
Section: Habitat Suitabilitymentioning
confidence: 98%